2016
DOI: 10.1071/an15025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of late gestation bodyweight change and condition score on progeny feedlot performance

Abstract: Inadequate nutrient intake during late gestation can cause cow bodyweight (BW) loss and influence cow reproductive performance and subsequent productivity of steer progeny. Therefore, a 7-year study with a 3 · 3 ar r angement of treatments was conducted at Corona Range and Livestock Research Centre, Corona, New Mexico to evaluate the effects of cow BW change and body condition score (BCS) during late gestation on subsequent cow pregnancy rates, progeny steer feedlot performance, and health. Cows were retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
3
5
0
1
Order By: Relevance
“…However, cows that have been adapted and managed to reproduce in harsh, limited nutrient environments may have the ability to maintain normal fetal growth and development during periods of maternal nutrient restriction. For instance, late gestation BW change from losing 25 kg to gaining 25 kg had no impact on calf weaning BW, BW at feedlot entry, finishing BW, and hot carcass weight (Mulliniks et al, 2016), illustrating that moderate restriction during late gestation did not affect progeny growth from birth throughout the finishing period. Maternal undernutrition in gestating ewes adapted to nutrient restricted environments did not affect fetal plasma concentrations of glucose or fetal growth (Vonnahme et al, 2006) and were able to maintain fetal concentrations of amino acids (Jobgen et al, 2008).…”
Section: Adipose Tissue Mobilization and Metabolic Flexibilitymentioning
confidence: 95%
See 1 more Smart Citation
“…However, cows that have been adapted and managed to reproduce in harsh, limited nutrient environments may have the ability to maintain normal fetal growth and development during periods of maternal nutrient restriction. For instance, late gestation BW change from losing 25 kg to gaining 25 kg had no impact on calf weaning BW, BW at feedlot entry, finishing BW, and hot carcass weight (Mulliniks et al, 2016), illustrating that moderate restriction during late gestation did not affect progeny growth from birth throughout the finishing period. Maternal undernutrition in gestating ewes adapted to nutrient restricted environments did not affect fetal plasma concentrations of glucose or fetal growth (Vonnahme et al, 2006) and were able to maintain fetal concentrations of amino acids (Jobgen et al, 2008).…”
Section: Adipose Tissue Mobilization and Metabolic Flexibilitymentioning
confidence: 95%
“…Thus, livestock that have experienced homeorhetic changes are better adapted to prioritize productivity and may be more efficient at mobilizing and oxidizing adipose tissue supplies (Rhoads et al, 2013). In a 7-yr study, Mulliniks et al (2016) categorized cows by their natural variation in BW change during late gestation as cows that lost 25 kg, maintained BW, or gained 25 kg. Cows that lost or maintained BW during late gestation had greater pregnancy rates the subsequent breeding season.…”
Section: Adipose Tissue Mobilization and Metabolic Flexibilitymentioning
confidence: 99%
“…During periods of low energy intake, mobilization of maternal nutrient lipid reserves is needed to offset energy imbalances of gestation. In a 7-yr study, Mulliniks et al (2015b) reported overall pregnancy rates were greater in cows either losing or maintaining BW during late gestation compared with cows gaining BW. Although BW change differences were not reported up to and through breeding, this improved reproductive performance may be attributed to a decrease in nutrient requirements in cows losing BW during late gestation and an overall increase in nutrient utilization.…”
Section: Adaptive Capacity and Metabolic Flexibilitymentioning
confidence: 99%
“…Además, el extracto de etéreo y la humedad del músculo Longissimus fue similar entre los novillos BP y AP (P> 0,10; Cuadro 4). Estos resultados respaldan estudios previos en vacas que fueron restringidas durante la gestación tardía (Underwood et al, 2010;Mulliniks et al, 2016;Stalker et al, 2006;Shoup et al, 2015), gestación media (Mohrhauser et al, 2015) o gestación temprana (Long et al, 2010). Se ha planteado la hipótesis de que la etapa fetal es el período de desarrollo más eficiente para aumentar el marmoleo en la carne de la descendencia (Du et al, 2010).…”
Section: Tratamientosunclassified